Interdisciplinary Approaches to Health: The Role of Nutrition, Radiology, Sociology, and Laboratory Science in Comprehensive Patient Care - Mansour Saleh Alduhami; Abdullah Sulaiman Almuzaini; Abdulsalam Saleh Alduhami; Khalid Saleh Alduhami; Hamza Soliman Alghufily; Abdulmonem Mohammed Alduhami; Mohmmed Saleh Alduhami; Abdullah Nasser Alrumayh (International Journal of Medical Toxicology and Legal Medicine, 2024)
The complexity of today's healthcare systems apparently urges a team-oriented and interdisciplinary approach to patient care. Modern medical science has come to realize that the needs of the patient transcend the boundaries of an isolated intervention on the part of specialists. Each one of these disciplines-nutrition, radiology, sociology, laboratory science-all provide something unique and irreplaceable that allows them to attain a comprehensive overview of health within all its biological, psychological, and social dimensions. The following paper attempts to discuss the four major roles these disciplines play in the delivery of comprehensive, patient-centered healthcare. Nutritional sciences provide a foundation for physical health; the sum of diet plays an important role in the prevention of chronic diseases and in many recovery processes. Meanwhile, radiology provides much-needed diagnostic capability: the ability to visualize internal conditions and disease processes and/or their progression is critical to diagnosis and treatment. While sociology provides awareness of the social determinants, it realizes the socioeconomic backgrounds and varying cultural influences and access to health care services in major influencers in patients' behaviors and health outcomes and their ability to adhere to treatment plans. Laboratory science, with accurate diagnostic testing, allows for personalized care along with the monitoring of disease markers through specific biochemical information. This paper highlights the contribution of each discipline and, therefore, stands in support of an integrated, holistic approach for better patient outcomes and improvements in the patient experience. All these fields combined together weave a necessary, smooth integration of health professionals into a sophisticated understanding of the patient needs beyond those of symptomatic and diagnostic consideration. Combined, these perspectives enable more tailor-made care and have the potential to lead healthcare systems toward treatment that is not only medically appropriate but also compassionate and responsive to a patient's life situation.